A Review of Tunable Electromagnetic Metamaterials With Anisotropic Liquid Crystals - Xu, Jing; Yang, Ruisheng; Fan, Yuancheng; Fu, Quanhong; Zhang, Fuli (Frontiers in Physics, 2021)
The performance of metamaterial is limited in designed narrow band due to its resonant nature, it is highly desirable to incorporate active inclusions in metamaterials to extend the operation bandwidth. This review summarizes the development in realizing tunability of electromagnetic response in metamaterials incorporated with nematic liquid crystal (LC). From rigorous comparison, it is found that the anisotropic property of nematic LC is essential to predict the influence of LC molecular director orientation on the resonant frequency of metamaterials. By carefully designing the metamaterials and properly infiltrating LC, the operation frequency of single/double negative parameters of metamaterials can be dynamically modulated with remarkable red/blue-shift, depending on the LC molecular orientation angle. Moreover, the recent liquid-crystal-based developments and novel applications are investigated and highlighted.